Therapeutic Targeting of Immune Cell Autophagy in Multiple Sclerosis: Russian Roulette or Silver Bullet? - Yang, Guan; Van Kaer, Luc (Frontiers in Immunology, 2021)
Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system (CNS) in which the immune system damages the protective insulation surrounding nerve fibers that project from neurons. The pathological hallmark of MS is multiple areas of myelin loss accompanied by inflammation within the CNS, resulting in loss of cognitive function that ultimately leads to paralysis. Recent studies in MS have focused on autophagy, a cellular self-eating process, as a potential target for MS treatment. Here, we review the contribution of immune cell autophagy to the pathogenesis of experimental autoimmune encephalomyelitis (EAE), the prototypic animal model of MS. A better understanding of the role of autophagy in different immune cells to EAE might inform the development of novel therapeutic approaches in MS and other autoimmune and inflammatory diseases.